USING MICROORGANISMS FOR SOIL PURIFICATION FROM HIGH-PARAFFIN CRUDE OIL - Gusman Kenzhetayev; Boranbayeva Assiya Nyrlubaevna; Syrlybekkyzy Samal; Serikbayeva Akmaral; Talgat Issanov (Academic Journal of Physical and Chemical Sciences, 2021)
This paper presents the research data aimed at resolving the problem of soil purification from highparaffin crude oil using microorganisms.Samples of oilcontaminated soil were taken from the walls of the oil storage pit at the Uzen oilfield. According to the analysis of the oilcontaminated soil samples, the share of oil was 28 %, the share of mechanical impurities – 9.7 %, and the share of water – 60 %.It has been found that according to the API(American Petroleum Institute) indicators, that oil chemical composition may contribute to its rapid decomposition during bioremediation. Paraffin hydrocarbons are also easily decomposed by bacteria. The bacterial preparation «SHER» was used in laboratory experiments.The method of bacteria immobilization with the «SHER» biological product on the medium made from screenings of shell limestone wastes has been chosen.The conditions for conducting experimental laboratory studies on cleaning oil-contaminated soils by biological remediation are described.According to the results of the research, it was established that the immobilization of bacteria of the biological product "Sher" by a carrier in the form of sifting limestone-shell rock showed a high degree of purification of oil-contaminated soil (88.63%).To study the further activity of bacteria, experiments were conducted on the secondary use of thesolution of residual mother waterof the biological product "SHER", used in the process of cleaning oil-contaminated soil.The results of experimental studies using solution of residual mother water and immobilization by screening showed the degree of soil purification (45.7%). Thus, based on the results of studies of the drug "SHER", it can be concluded that this drug can effectively neutralize oil products in the soil.